Entero-vesical fistulas in CROHN'S disease: A case series report and review of the literature. (2017) - Vagianos, Costantine; Malgarinos, George; Spyropoulos, Charalampos; Triantafillidis, John K.
Highlights: Entero-vesical fistulas (EVFs) represent an uncommon complication of Crohn's disease. EVFs affects mostly men patients. Conservative treatment improves symptoms but is associated with low rate of healing. Surgical approach is usually necessary, establishing long-term remission. Abstract: Background: Entero-vesical fistula (EVF) is an abnormal link between the enteric lumen and the urinary bladder. Crohn's disease (CD) represents, nowadays, the most common cause in the formation of this fistula. Materials and methods: The aim of this study was to describe the diagnostic and treating modalities applied in nine patients with CD and EVFs, the clinical/epidemiological features of this clinical entity and to perform a systemic review of the literature, concerning the diagnosis and treatment of this complication. Results: The medical records of eight men and one woman (mean age 42 ± 12 years) with EVFs were analyzed. The terminal ileum and the ileocecal region were affected in three and six cases, respectively. The most common symptoms were pneumaturia, fecaluria, fever, urinary urgency and abdominal pain. The diagnosis was suspected by abdominal CT scan and by indirect findings of bladder infection in cystoscopy. MRI with concurrent cystography set the diagnosis in three patients. Colonoscopy was not helpful. Conservative treatment, including administration of antibiotics and immunosuppressive agents in all patients and anti-TNF-a agent (infliximab) in six patients, was ineffective. Surgical treatment was applied in seven cases (77.8%), including fistula repair in all patients, drainage of coexistent intraabdominal abscess in two, small bowel resection in four and ileocecectomy in two cases. Conclusion: EFVs are uncommon but potentially dangerous complications of CD. Abdominal CT scan and cystoscopy are the most commonly used diagnostic modalities. Surgical treatment seems to be unavoidable in most cases, although medical treatment could also benefit a small cohort of patients.